2015
DOI: 10.3892/mmr.2015.3966
|View full text |Cite
|
Sign up to set email alerts
|

Expression of podoplanin and vimentin is correlated with prognosis in esophageal squamous cell carcinoma

Abstract: Podoplanin is a small membrane mucin, which is involved in cell migration and cancer cell invasion. However, the roles of podoplanin in esophageal squamous cell carcinoma (ESCC) are poorly understood. In the present study, 139 cases of surgically resected ESCC were analyzed and the clinicopathological significance of podoplanin membrane expression in ESCC was demonstrated. Podoplanin expression was positive in 66.2% (92/139) of ESCC samples; with weak expression in 32.4% (45/139), and strong expression in 33.8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
31
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 25 publications
8
31
0
1
Order By: Relevance
“…According to progression of cancer, cancer cells seems to acquire the ability of invasion and metastasis by EMT (24). Several studies already suggested that Wnt signaling pathway closely related to EMT (25,26), and EMT related factors would be prognostic factors of ESCC (27,28). These studies support the hypothesis that the canonical Wnt signaling pathway activates the progression and metastasis of ESCC through the EMT; whether Wnt3a expression might also be correlated with the progression and metastasis of ESCC should be investigated.…”
Section: Discussionsupporting
confidence: 68%
“…According to progression of cancer, cancer cells seems to acquire the ability of invasion and metastasis by EMT (24). Several studies already suggested that Wnt signaling pathway closely related to EMT (25,26), and EMT related factors would be prognostic factors of ESCC (27,28). These studies support the hypothesis that the canonical Wnt signaling pathway activates the progression and metastasis of ESCC through the EMT; whether Wnt3a expression might also be correlated with the progression and metastasis of ESCC should be investigated.…”
Section: Discussionsupporting
confidence: 68%
“…Despite the improvement in treatment throughout the past decades, the prognosis of ESCC patients remains poor, with a 5‐year survival rate of approximately 20–30% . The high mortality rate is largely attributed to aggressive invasion and metastasis of ESCC cells . Hence, a better understanding of the molecular mechanisms relating to cancer invasion and metastasis is critical for improving the prognosis of patients with ESCC.…”
mentioning
confidence: 99%
“…Strong podoplanin expression was significantly correlated with peripheral type (P < 0.001), with a correlation coefficient of 0.678. Recently, podoplanin has been considered as one of the candidate markers of cancer stem cells, associated with cancer cell invasion or migration, as well as the prognosis of several cancers (12,24,28,29,33). Several studies have clarified that podoplanin expression promotes epithelial-to-mesenchymal transition in morphogenetic processes.…”
Section: Relationships Between Podoplanin Intensity and Localizationmentioning
confidence: 99%
“…Immunoreactivity was detected using the avidin-biotin method (Vectastain Elite ABC kit; Vector Laboratories, Inc., Burlingame, CA). We evaluated the existence of specific immunostaining prior to the immunohistochemical staining in this study (29).…”
mentioning
confidence: 99%